Log in to add a comment

## Answers

**Answer:**We use the Sum of 2 Cubes formula given above.64x3 + 125= (4x)3 + (5)3= (4x + 5)[(4x)2 − (4x)(5) + (5)2]= (4x + 5)(16x2 − 20x + 25)As mentioned above, we cannot factor the expression in the second bracket any further. It looks like it could be factored to give \displaystyle{\left({4}{x}-{5}\right)}^{2}(4x−5)2, however, when we expand this it gives:\displaystyle{\left({4}{x}-{5}\right)}^{2}={16}{x}^{2}-{40}{x}+{25}(4x−5)2=16x2−40x+25This "perfect square trinomial" is not the same as the expression we obtained when factoring the sum of 2 cubes.ExercisesFactor:(1) x3 + 27Answer(2) 3m3 − 81